Sensoriamento ótico para medição de nível, velocidade e vazão no escoamento em canais - Fernandes, Diego (2022)
This work aimed to create a transducer based on sensors with Bragg gratings (FBG) for simultaneous measurements of water level, velocity and temperature in channels. Optical fibers are glued to a rectangular aluminum rod that has been attached to the bottom of a rectangular channel. The flow of water causes a distributed force and characteristic curve in the rod, depending on the fluid level and velocity. A set of four FBGs are used to monitor the flexural profile of the rod. With the difference between the wavelengths of the FBGs, it is possible to eliminate the effect of temperature and obtain a system of nonlinear equations dependent only on the speed and water level. They were worked with speeds between 0.1 m/s to 0.9 m/s and water levels from 0.4 m to 0.7 m, for the evaluated experiments. An empirical model was obtained to describe the change in wavelength and, as a consequence, the level and velocity of the water. Until the final presentation of this work, it was not possible to find satisfactory precision results for more than 30% of the systems and expectations for future work remained. Then artificial neural networks were used as a more direct solution to determine the level and speed of water from the measured wavelengths, considering mean values and standard deviation. With this method, the maximum absolute deviations were 0.02 m/s and 3.1 cm, for the mean velocity and water level, respectively.